The Effect of Ecological Succession on The Physical and Chemical Properties of Gaberoun Lake, South of Libya - Mona Alasagir,; Abdul Salam Almathnani,; Fatima Al-Imam,; Embarak Al-Amin,; Hala Youssef, (AlQalam Journal of Medical and Applied Sciences, 2024)
This study was conducted on Lake Kabaroun, located in the Ubari region in southern Libya, with the aim of evaluating the effect of environmental succession on the physical and chemical properties of the water of Lake Kabaroun.The results showed that the lake's water was transparent on the eastern side. Its pH ranges between (9.45 - 10.31 pH), meaning that the lake water is alkaline. Total dissolved salts (TDC) were estimated at (90.59-115.28 mg/L), which made dissolved oxygen relatively low (5.08 - 6.88 mg/L). The results also showed that the lake water contained a high concentration of SiO3 (3.46-6.91 mg/L), as well as nutrients. The concentration of NO3 (316.67 – 408.33 mg/L) and PO4 (17.83 – 72 mg/L) was. The study also recorded the presence of a very weak plant diversity, represented by the presence of the reed swamp plant, Phragmite australis, which is considered the most dominant species around the lake, which gives a clear indication of its presence in the reed swamp stage. As for the Cyperus Laevigatus plant, its presence indicates the presence of the sedgem eadow stage of ecological succession, while the presence of the tamarisk plant, Tamarix aphylla, indicates the presence of the shrubby stage of ecological succession. It is clear from the results of a study that the continued increase in plant growth creates an environmental habitat that allows the emergence of biodiversity for different animal species, such as insects, spiders, and birds. Human activities also have an impact on the development of the succession process in the lake. All of these indicators indicate the development and continuation of the ecological succession process in the lake and contribute to its extinction. أجريت هذه الدراسة علي بحيرة قبرعون الواقعة بمنطقة اوباري جنوب ليبي. وبهدف إلى تقييم تأثير التعاقب البيئي على الخواص الفيزيائية والكيميائية في مياه بحيرة قبرعون. أظهرت النتائج تميز مياه البحيرة بالشفافية في الجهة الشرقية، والأس الهيدروجيني pH بها الذي تراوح ما بين (9.45 – 10.31 pH)، أي أن مياه البحيرة قلوية. قدرت الأملاح الذائبة الكليةTDC بها (90.59 – 115.28 ملجم/لتر) مما جعل الأكسجين الذائب منخفضاً نسبياً (5.08 -6.88 ملجم /لتر). كما أظهرت النتائج احتواء مياه البحيرة علي تركيز عالي من السيليكات (3.46-6.91 ملجم/لتر)، وأيضاً المغذيات فقد كان تركيز النترات (316.67 – 408.33 ملجم/ لتر) والفوسفات (17.83 – 72 ملجم / لتر)، وسجلت الدراسة أيضاً وجود تنوع نباتي ضعيف جداً تمثل في تواجد نبات القصبة Phragmite australisالذى يعتبر أكثر الأنواع سيادة حول البحيرة وهو يعطى دلالة واضحة على وجوده في مرحلة المستنقع القصبيي Reed swamp stage، أما نبات السمار Cyperus Laevigatus فيعطي دليل علي وجوده طور المروج Sedgemeadow stage من التعاقب البيئي، في حين نبات الأثل Tamarix aphyllaوجوده يدل علي الطورالشجيري Shrubby stage للتعاقب البيئي. يتضح من نتائج دراسة أن استمرار زيادة نمو النباتات تعطي موطن بيئي يسمح بظهور تنوع حيوي لأنواع حيوانية مختلفة كالحشرات والعناكب والطيور. كما أن للأنشطة البشرية أثر على تطور عملية التعاقب في البحيرة. جميع هذه المؤشرات تدل علي تطور واستمرار عملية التعاقب البيئي في البحيرة وتساهم في اندثارها.